2021
DOI: 10.1557/s43580-021-00122-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hetero- and homo-nanostructure on the hydrogen embrittlement resistance in heavily deformed 316LN austenitic stainless steel

Abstract: The heterogeneous and homogeneous nanostructured 316LN austenitic stainless steel with tensile strengths of approximately 1.8 and 2.0 GPa were fabricated by 92% heavy cold rolling and high-pressure torsion straining, respectively. The influence of heterogeneous and homogenous nanostructures on the resistance to hydrogen embrittlement was investigated. Thermal desorption spectroscopy of the electrochemical hydrogen-charged specimen showed that both nanostructures exhibited almost the same concentration of diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The presence of inclusions and nanostructures can increase the hydrogen resistance and fracture toughness of steel [78][79][80]. For example, chemical heterogeneity in highstrength steel can significantly increase fracture resistance and ductility in hydrogencontaining environments [78].…”
Section: Literature Survey: State-of-the-artmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of inclusions and nanostructures can increase the hydrogen resistance and fracture toughness of steel [78][79][80]. For example, chemical heterogeneity in highstrength steel can significantly increase fracture resistance and ductility in hydrogencontaining environments [78].…”
Section: Literature Survey: State-of-the-artmentioning
confidence: 99%
“…For example, chemical heterogeneity in highstrength steel can significantly increase fracture resistance and ductility in hydrogencontaining environments [78]. The effect of heterogeneous and homogeneous nanostructures on the resistance to hydrogen embrittlement in steel [79] in a thermodynamic-based model to analyze hydrogen capture at the inclusion-matrix interface showed its dependence on the strength of the steel matrix [80]. An examination of the effect of sulfide inclusions on the mechanical properties of steel showed that inclusions have a detrimental effect on fatigue resistance [81].…”
Section: Literature Survey: State-of-the-artmentioning
confidence: 99%
See 2 more Smart Citations